Serum Beta HCG and uterine artery Doppler studies in second trimester to predict preeclampsia and eclampsia - Kulkarni, Nitin; Bansal, Radhika; Pawar, Pankaj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive disorders during pregnancy remain amongst the most significant and intriguing unsolved problems in obstetrics. The study aims at testing the hypothesis that women with high serum beta hCG levels and alterations in waveforms in the uterine artery doppler in early second trimester have high risk of developing pre-eclampsia. Methods: Serum Beta hCG estimation was done by Sandwich chemiluminescence immunoassay method. All uterine artery waveforms were obtained using a Toshiba nemio ultrasound machine attached to a 3.5 MHz curvilinear transducer, with colour and pulsed Doppler abilities. Results: For prediction of preeclampsia or eclampsia uterine artery Doppler velocimetry alone shows specificity of 96.30%, sensitivity of 90%, positive predictive value of 94% and negative predictive value of 80%. When it is combined with serum beta HCG sensitivity and specificity are almost same, but alone serum beta HCG levels are showing sensitivity of 96% and specificity of just 76%. Conclusions: Abnormal waveforms on uterine Doppler studies are the better predictors for preeclampsia and eclampsia when done in early second trimester.